Do Perfectionism Traits Predict Team Cohesion and Group Conflict Among Youth Athletes?. Issue 3 (June 2022) - Freire, Gabriel Lucas M.; Fiorese, Lenamar; Moraes, José Fernando V. N. d.; Codonhato, Renan; Oliveira, Daniel Vicentini de; Nascimento Junior, José Roberto de A. d.
In this cross-sectional study, we investigated the predictive power of perfectionism on 413 Brazilian athletes' perceptions of team cohesion and conflict. Participants responded to the Sport Multidimensional Perfectionism Scale-2, the Youth Sport Environment Questionnaire, and the Group Conflict Questionnaire. In data analysis, we used Pearson correlations, multiple regression, latent profile analysis (LPA), and multiple analysis of variance. Regression analysis revealed that perfectionistic standards were positively associated with both task and social cohesion ( p < .01), while doubts about action were negatively associated with task cohesion ( p < .01). Furthermore, concern over mistakes, parental pressure, and doubts about action were positively associated with social conflict ( p < .01), and concern over mistakes was positively associated with task conflict ( p < .01). LPA revealed two profiles of perfectionism that we termed perfectionistic concerns and perfectionistic striving. Perfectionistic striving was positively correlated with social cohesion ( p < .001), and perfectionistic concerns were positively correlated with both task conflict ( p < .001) and social conflict ( p < .001).